A balancing act in sports: How cognitive skills contribute to better gymnastic performance - Firmansyah, H.; Hendrianto, R.; Negara, J. D. K.; Martini, T. (Science of Gymnastics Journal, 2024)
Professional trainers and athletes often neglect the importance of cognitive skills yet they are arguably among the keys to improving athletes` performance. This study aims to investigate the role of cognitive skills in gymnasts` performance using the correlational method. The research study included thirty-seven young gymnasts (average age of 18.64 ± 0.83 years old) who regularly participated in and were preparing for competitions. Research data were collected from cognitive skills tests and gymnastic performance reviewed by a professional jury. The findings of this study show that better cognitive abilities led to better gymnastic performance, emphasizing the importance of attention, concentration, memory, visuospatial, language, and executive functions. Further research could longitudinally examine the development of athletes` cognitive skills and focus on implementing cognitive training to enhance gymnastic performance.